Penyuluhan Faktor Risiko Dan Gejala Stroke - Yudhisman Imran; Irmiya Rachmiyani; Donna Adriani; Mustika Anggiane Putri; Patwa Amani; Dina Putri Nasution (CV. Multi Kreasi Media, 2024)
Stroke is an emergency disease in the field of neurology. Stroke is acute and one of the highest causes of disability and death in various countries in the world. There has been an increase in the incidence of stroke in various countries. Stroke may occur due to risk factors. Stroke risk factors are divided into modifiable (hypertension, diabetes mellitus, smoking, dyslipidemia) and non-modifiable risk factors (age, gender, ethnicity). Based on the pathophysiology, stroke is divided into two, namely ischemic stroke (blockage) and hemorrhagic stroke (bleeding). Stroke symptoms are characterized by sudden neurological deficits. Examples of neurological deficits are mouth, mumbling, slurred speech, weakness on one side of the body, and numbness on one side of the body. This education aims to increase public knowledge about the risk factors and symptoms of stroke so that they can prevent disability and death as a result of stroke. The education method is to fill out a questionnaire by 30 participants before and after online education via Zoom video conference meeting. Education was held in Duren Sawit Subdistrict RT 002/04 because many residents had experienced strokes, some even had repeat ones. The results of the level of knowledge before education were 66.25% correct answers. The results of the level of knowledge after education were 71.88% correct answers. Based on the results above, it can be concluded that education could increase public knowledge.